Just a hint, Clint - Foster Lori 1958 (New York : Brava/Kensington Pub., 2004)
When Clint Evans takes on the four thugs holding heiress Julie Rose hostage, he isn't thinking about the danger. What's got Clint in a lather is Julie herself.
Includes a preview of Alison Kent's new five-episode series (p. [281]-295).
Keywords: Teachers -- Fiction; Soldiers of fortune -- Fiction; Rich people -- Fiction; Kidnapping -- Fiction; Adventure fiction; Love stories